The generaltion gap in nursing - J.G.P. van Niekerk (AOSIS, 1984)
Generation gap is one of those catch phrases that we so often use, and misuse, to excuse ourselves or to cover up for our shortcomings. It is like the shortage of nurses behind which we hide from all our nursing problems. Although it is such a commonly used phrase, do we really know what it means? When you consult the Oxford Dictionary, you will find that it defines generation gap as: differences of opinion between those of different generations. It will surprise most people that the generation gap becomes a problem only when there are differences of opinion.